COMPENSATION AS THE AIM OF THE CONTRIBUTION TO THE FUND OF CRIME VICTIMS - Levon, Justyna (Teisė, 2017)
Author analyses the penal effect measure called contribution to the fund of a crime victims, which was implemented in the Criminal Code of the Republic of Lithuania in 2000. Article identifies the compensational aim of this measure and its meaning to the State compensation system for damages caused by violent crimes.